Analisis Financial Distress dalam Memprediksi Kebangkrutan pada Perusahaan Investasi yang Terdaftar pada Bursa Efek Indonesia Tahun 2016 – 2020 - Cyntia Carolina (JAKU (Jurnal Akuntansi & Keuangan Unja) (E-Journal), 2023)
This study aims to determine whether investment companies listed on the Indonesia Stock Exchange for the 2016-2020 period have the potential for abnkruptcy based on the Altman Z-Score method. Prediction of bankruptcy is needed by companies in order to determine the viability of the company. This study uses secondary data obtained from the financial statements of six investment companies listed on the Indonesia Stock Exchange for the 2016-2020 period that have met the criteria to be used as research samples. This bankruptcy prediction analysis uses the Altman Z-Score formula to determine the condition of the company. There are categories of Z-Score, 1) Z-Score < 1,1 means dangerous or bankrupt, 2) 1,1 < Z-Score < 2,6 means gray or vulnerable, 3) Z-Score > 2,6 means safe. Based on the result of the study, it shows that: the condition of investment companies listed on the IDX in 2016-2020 is in a dangerous.